2019
DOI: 10.1038/s41598-019-39473-y
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric NANOG repressors inhibit glioblastoma growth in vivo in a context-dependent manner

Abstract: Targeting stemness promises new therapeutic strategies against highly invasive tumors. While a number of approaches are being tested, inhibiting the core transcription regulatory network of cancer stem cells is an attractive yet challenging possibility. Here we have aimed to provide the proof of principle for a strategy, previously used in developmental studies, to directly repress the targets of a salient stemness and pluripotency factor: NANOG. In doing so we expected to inhibit the expression of so far unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Other studies investigated synergistic therapeutic effect of targeting NANOG with cancer vaccination or with chemotherapeutic drugs, where an increased sensitivity for drugs and an induced cell apoptosis was observed. 7275 Information regarding Nanog-targeting therapy in human cancer is limited, i.e. there is an ongoing clinical trial (phase 2) with NANOG inhibitor in combination with sorafenib in adult patients with hepatocellular carcinoma.…”
Section: Nanog As a Treatment Targetmentioning
confidence: 99%
“…Other studies investigated synergistic therapeutic effect of targeting NANOG with cancer vaccination or with chemotherapeutic drugs, where an increased sensitivity for drugs and an induced cell apoptosis was observed. 7275 Information regarding Nanog-targeting therapy in human cancer is limited, i.e. there is an ongoing clinical trial (phase 2) with NANOG inhibitor in combination with sorafenib in adult patients with hepatocellular carcinoma.…”
Section: Nanog As a Treatment Targetmentioning
confidence: 99%
“…This may suggest that the mechanism of anastasis may suppress stemness properties of GBM cells. NANOG and WNT5A upregulation may lead to a more aggressive phenotype of the cells as independently from the stemness feature (11,12). Moreover, these results also indicated that the cells may become stem-like cells by gaining a self-renewal property (13).…”
Section: Discussionmentioning
confidence: 78%
“…Because our work is directed toward the identification of biomarkers for the early diagnosis of GBM, we focused on CACLR, considering its cellular functions as a tumor suppressor, which are currently little known, and its ability to interact with various chaperone molecules, including some belonging to the Hsp70 family ( Figure 4 B). Furthermore, our proteomic analysis identified proteins involved in the canonical and alternative complement pathways, in the metabolic pathway, in inflammatory pathways, and more (additional information is presented in Table S3 [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]). The differentially expressed proteins were further analyzed using the STRING database to derive an interaction network and potential signaling pathways, which may reveal the tumorigenic mechanism underlying GBM ( Figure 4 B).…”
Section: Discussionmentioning
confidence: 99%